2016
DOI: 10.3109/09273948.2015.1132739
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Dry Eye and Sjögren Syndrome in Patients with Migraine

Abstract: Dry eye symptoms and findings are higher in migraine patients when compared with the healthy subjects without the presence of Sjögren syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Several studies have found that patients with migraine are more likely to report dry eye symptoms than controls 1315 and that severity of dry eye symptoms correlates with migraine severity. 8 Interestingly, some studies have reported that dry eye symptoms correlate with dry eye signs, such as decreased tear break-up times and reduced Schirmer’s testing, 1415 while others have not found such significant differences. 13 Despite mixed evidence, these two disease entities are clearly associated with one another.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that patients with migraine are more likely to report dry eye symptoms than controls 1315 and that severity of dry eye symptoms correlates with migraine severity. 8 Interestingly, some studies have reported that dry eye symptoms correlate with dry eye signs, such as decreased tear break-up times and reduced Schirmer’s testing, 1415 while others have not found such significant differences. 13 Despite mixed evidence, these two disease entities are clearly associated with one another.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Sarac et al observed a higher prevalence of dry eye in 50 migraine patients compared to age- and sex-matched healthy subjects. The authors speculated that dryness of the ocular surface may activate the trigeminal nerve to cause reflex lacrimation, and the activation of the trigeminal nerve may trigger migraine headache [ 207 ].…”
Section: Headache and Connectivitismentioning
confidence: 99%
“…Among previous investigations regarding the link between DED and migraine headaches, some have demonstrated an association between the 2 disorders . Objective and clinical variables used to assess the presence and severity of DED, such as tear osmolarity, tear film breakup time, and Schirmer testing results, can also differ significantly between patients with migraine headaches and control individuals without the disorder .…”
Section: Introductionmentioning
confidence: 99%
“…5 Among previous investigations regarding the link between DED and migraine headaches, some have demon-strated an association between the 2 disorders. 6,7 Objective and clinical variables used to assess the presence and severity of DED, such as tear osmolarity, tear film breakup time, and Schirmer testing results, can also differ significantly between patients with migraine headaches and control individuals without the disorder. [8][9][10] Although prior studies in this area shed some light on the possible link between migraine headaches and DED, they possess inherent limitations.Such studies, including some of those cited above, 2,7 are population-based cross-sectional studies that rely on patientreported, subjective assessments of disease symptoms, such as questionnaires or surveys.…”
mentioning
confidence: 99%